Microstructure analysis of periapical area in abscess patients before and after endodontic treatment - Dona, Adriani Prima; Wulansari, Dwi Putri (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: The study aims to analyze the microstructure of the alveolar bone in the periapical area by knowing the area of the lesion, the number of particles, and the area of the particles in patients before and after endodontic treatment in the diagnosis of inflammatory periapical abscess lesions through digitizing periapical radiographs using ImageJ software. By using this approach, it is hoped that more objective and accurate data can be obtained in evaluating changes that occur in periapical lesions, thereby improving the overall quality of endodontic treatment. Materials and Methods: This research uses an observational analysis design using the paired t-test and the Wilcoxon. Samples were taken using a purposive sampling technique, namely 28 pairs of periapical radiographs before and after endodontic treatment, with a diagnosis of periapical abscess carried out at Hasanuddin University Dental Hospital in the period February-April 2024, who met the radiographic inclusion criteria were included in this study. Results: The results showed that from 28 pairs of, there was a decrease in the average lesion area from 20.00 ± 16.71 to 18.19 ± 6.92mm2, an increase in the average number of particles from 4.89 ± 2.15 to 4.93 ± 1.82, and an increase in the average area of particles from 130.14 ± 2.15mm2 to 131.82 ± 24.28 mm². Conclusion: The conclusion of this research is that there was a difference in decreasing the area of the lesion, the number of, but the results were not significant within three months during endodontic treatment. Minimal changes are obtained from the minimal and particles produced. Keywords: Periapical abscess, digitization of periapical radiographs, ImageJ software